Preparation of Renewable Thiol‐Yne "Click" Networks Based on Fractionated Lignin for Anticorrosive Protective Film Applications. Issue 13 (17th March 2022) - Jedrzejczyk, Monika A.; Madelat, Negin; Wouters, Benny; Smeets, Hans; Wolters, Maartje; Stepanova, Svetlana A.; Vangeel, Thijs; Van Aelst, Korneel; Van den Bosch, Sander; Van Aelst, Joost; Polizzi, Viviana; Servaes, Kelly; et al.
Abstract: The synthesis of novel, renewable lignin‐based protective films with anticorrosive properties is presented in this work. Thermosetting films are prepared by means of tandem UV‐initiated thiol‐yne "click" synthesis and Claisen rearrangement strategy. These films contain high lignin loading, 46–61%, originating from a nickel‐catalyzed birch wood reductive catalytic fractionation (RCF) process. Lignin fractions with varying monomer content are compared before resins preparation, namely a mixture of monomers and oligomers without fractionation, or after fractionation via extraction and membrane separation. This study aims to determine if the separation of lignin monomers and oligomers is necessary for the application as a thermosetting resin. The resulting films exhibit remarkable adhesion to a metal surface and excellent solvent resistance, even after exposure to a corrosive environment. Moreover, those films show superior barrier properties, studied with odd random phase electrochemical impedance spectroscopy (ORP EIS). After 21 days of exposure, the examined films still show impressive high corrosion protection with the low‐frequency impedance ≈10 10 Ω cm 2 and capacitive behavior. This work demonstrates an interesting proof‐of‐concept where laborious, costly, and energy‐intensive separation of the depolymerized lignin mixture of monomers and oligomers is not necessary for the successful resin synthesis with excellent properties using the applied synthetic strategy. Abstract : This work shows an example of the preparation of depolymerized and fractionated lignin‐based thermosets with anticorrosive properties. Lignin monomers and oligomers fractionation by membrane separation and extraction is investigated and benchmarked with unseparated mixture. Lignin fractions are crosslinked using tandem thiol‐yne chemistry and Claisen rearrangement approach. The obtained films show excellent adhesion to metal surface, solvent resistance, and anti‐corrosive performance.